Fortalecimiento institucional y expansión del crédito mediante el uso de TICs en Entidades Financieras Comunales en Bolivia - Boris Sergio Branisa Caballero; Carlos Gustavo Machicado; Mario Marcelo Arduz Rejas (Institute for Advanced Development Studies (INESAD), 2018)
– This document analyzes the implementation of a financial system (software) for the Community Financial Institutions (CFEs) carried out between 2011 and 2012. The system was a set of financial modules that facilitated the administration of information and operational practices in each one of these entities. The use of the system was aimed at improving its institutional structure, as well as expanding its credits and increasing the income of its borrowers. By using qualitative methods (interviews) and quantitative data (Data Mart), it was possible to conclude that the system had benefits within the operational management of financial institutions, but it was not possible to demonstrate an evident impact in the increase of the credits and neither in the income of the borrowers.
Keywords: O30; G21; D20; 330; technological change; microfinance institutions; organization